New species of Echinobothrium van Beneden, 1849 (Cestoda: Diphyllidea) from Indo-Pacific maskrays (Neotrygon Castelnau) off Australia and Borneo - Dallares, Sara; Kuchta, Roman (Folia parasitologica, 2024)
Four new diphyllidean species of the genus Echinobothrium van Beneden, 1849 are described from Indo-Pacific maskrays (Neotrygon Castelnau, Dasyatidae). Echinobothrium giraffaeous sp. n. from Neotrygon leylandi (Last) off northern Australia, Echinobothrium ivanovae sp. n. from Neotrygon orientalis Last, White et Serét off Borneo, and Echinobothrium bethae sp. n. from Neotrygon varidens (Garman) off Borneo are distinguished from all but one of the 33 valid species of the genus by the possession of the outermost A hooks with an extended base into which the bases of the three outermost B hooks are inserted. Echinobothrium rhynchobati (Khalil et Abdul-Salam, 1989) is the only known species with this unique feature, but its rostellum has a system of interlocking knobs and sockets that articulate bases of the A and B type hooks with one another, which is not present in any of the newly described species. Echinobothrium tyleri sp. n. from Neotrygon australiae Last, White et Serét off northern Australia is distinguished from all known species of Echinobothrium by its unique rostellar hook formula {2-3 18/17 2-3}. With the present addition of four new species, the central Indo-Pacific realm becomes the major hotspot for Echinobothrium, from which 13 species have been reported.
Keywords: rejnokovití; Austrálie; Animals; Australia; nemoci ryb; zvířata; Fish Diseases; Cestoda; Skates, Fish; Borneo